2020
DOI: 10.1016/j.ymthe.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

CD39 Produced from Human GMSCs Regulates the Balance of Osteoclasts and Osteoblasts through the Wnt/β-Catenin Pathway in Osteoporosis

Abstract: Osteoporosis is a disease in which the density and quality of bone are reduced, causing bones to become weak and so brittle that a fall or even mild stresses can cause a fracture. Current drug treatment consists mainly of antiresorptive agents that are unable to stimulate new bone formation. Our recent studies have defined a critical role of gingiva-derived mesenchymal stem cells (GMSCs) in attenuating autoimmune arthritis through inhibition of osteoclast formation and activities, but it remains to be ruled ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 59 publications
(77 reference statements)
0
43
0
Order By: Relevance
“…This same group also found that an A2bAR agonist reduced bone loss in ovariectomized mice [ 52 ]. A more recent study reported CD39 on gingiva-derived mesenchymal stem cells as a promoter of osteogenesis through the Wnt/β-catenin signaling pathway [ 60 ].…”
Section: Regulation Of Adipogenesis and Osteogenesis By Bone Marromentioning
confidence: 99%
“…This same group also found that an A2bAR agonist reduced bone loss in ovariectomized mice [ 52 ]. A more recent study reported CD39 on gingiva-derived mesenchymal stem cells as a promoter of osteogenesis through the Wnt/β-catenin signaling pathway [ 60 ].…”
Section: Regulation Of Adipogenesis and Osteogenesis By Bone Marromentioning
confidence: 99%
“…MSCs are the most scientifically studied cells in regenerative medicine. They play a significant role in tissue regeneration and repair and generate local anti-inflammatory and healing signals ( Huang et al, 2017 ; Wu et al, 2020 ). Studies have shown that MSCs work through their paracrine effect, namely secreted EVs work.…”
Section: Msc-exosomesmentioning
confidence: 99%
“…Several studies have also shown that co-culture with mouse GMSCs can robustly suppress the differentiation of mouse naïve CD4 + T cells into Th1, Th2 or Th17 cells under different experimental conditions (58,59,62,65,67). Meanwhile, numerous in vivo studies have shown that systemic administration of either human (15,54,56,61,62,64,65,67,68,70,72) or mouse (51,58,59,63) GMSCs suppressed Th1, Th2, and/or Th17 cell differentiation and activity in various preclinical disease models. For instance, treatment with human GMSCs significantly reduced the frequency of Th2 and Th17 cells when compared to primary dermal fibroblast (PDF) treatment of lupus nephritis model in mice; meanwhile GMSCs also reduced T follicular helper (Tfh) cells in both spleen and lymph nodes (71).…”
Section: T Helper Cellsmentioning
confidence: 99%
“…Using a unique population of CD39 + GMSC play a critical role in promoting bone formation, whereby CD39 produced from GMSC exerted its osteogenic capacity through the Wnt/bcatenin pathway (72).…”
Section: T1dmmentioning
confidence: 99%